DNA binding in combination with capillary electrophoresis and inductively coupled plasma mass spectrometry for the rapid speciation analysis of mercury. Issue 1 (4th January 2018) - Chen, Yiquan; Chen, Lian; Wang, Xusheng; Xi, Zhiming; Wu, Yongning; Fu, FengFu
Abstract: We herein developed a method for the rapid speciation analysis of Hg 2+ and CH3 Hg + by using specific DNA sequences to bind Hg 2+ and CH3 Hg + together with capillary electrophoresis and inductively coupled plasma mass spectrometry. The specific DNA sequences can combine with Hg 2+ and CH3 Hg + with different binding force, which makes the formed DNA‐Hg 2+ and DNA‐CH3 Hg + conjugates possess different negative charges, and thus make Hg 2+ and CH3 Hg + can be more easily and rapidly separated by capillary electrophoresis under reverse mode. Under the optimal conditions, the Hg 2+ and CH3 Hg + can be baseline separated and detected by capillary electrophoresis‐inductively coupled plasma mass spectrometry within 11 min with a detection limit of 0.12 and 0.10 ng/mL, respectively. With the help of the method, we have successfully determined Hg 2+ and CH3 Hg + in dried fish muscle samples with a recovery of 95–101% and a relative standard deviation ( n = 6) <5%. In comparison with previous capillary electrophoresis and inductively coupled plasma mass spectrometry methods, the proposed method has shorter separation time and higher sensitivity under the same conditions of inductively coupled plasma mass spectrometry. Higher sensitivity and shorter separation time make our method a valuable technique to the speciation analysis of trace Hg 2+ and CH3 Hg + in the environmental and food samples.